1990
DOI: 10.3109/08923979009019679
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Human T Lymphocyte Function by Prothymosin α: Incremed Production of Interleukin-2 and Expression of Interleukin-2 Receptors in Normal Human Peripheral Blood t Lymphocytes

Abstract: The in vitro incubation of phytohemagglutinin (PHA)- or alloantigen-stimulated peripheral blood T cells with prothymosin alpha (ProT alpha) resulted in a marked and reproducible increase in the production of interleukin-2 (IL-2). Incubation of T cells with ProT alpha, in the absence of PHA or alloantigen, failed to induce any production of IL-2. ProT alpha by itself did not exert any IL-2 activity. Finally, ProT alpha was shown to increase the expression of IL-2 receptors on phytohemagglutinin- or alloantigen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 41 publications
0
12
0
3
Order By: Relevance
“…Numerous in vitro studies further confirmed the extracellular role of the polypeptide. As already aforementioned, peripheral blood T cells stimulated with proTα produced high amounts of IL-2 and increased the expression of IL-2 receptor on their surface (Baxevanis et al, 1990;Cordero et al, 1991), while APCs and DCs activated with proTα upregulated MHC class II and costimulatory molecules (CD11b, CD80, CD83, CD86, and CD40; Skopeliti et al, 2009), respectively. NK and LAK cells cultured in the presence of proTα augmented their cytotoxicity (Cordero, Sarandeses, López, & Nogueira, 1992;López-Rodríguez et al, 1994), and proTα-activated neutrophils showed increased chemotaxis, produced high amounts of ROS, and became cytotoxic against cancer cell targets (Heidecke, Eckert, Schulze-Forster, & Maurer, 1997;.…”
Section: The Extracellular Role Of Protαmentioning
confidence: 52%
“…Numerous in vitro studies further confirmed the extracellular role of the polypeptide. As already aforementioned, peripheral blood T cells stimulated with proTα produced high amounts of IL-2 and increased the expression of IL-2 receptor on their surface (Baxevanis et al, 1990;Cordero et al, 1991), while APCs and DCs activated with proTα upregulated MHC class II and costimulatory molecules (CD11b, CD80, CD83, CD86, and CD40; Skopeliti et al, 2009), respectively. NK and LAK cells cultured in the presence of proTα augmented their cytotoxicity (Cordero, Sarandeses, López, & Nogueira, 1992;López-Rodríguez et al, 1994), and proTα-activated neutrophils showed increased chemotaxis, produced high amounts of ROS, and became cytotoxic against cancer cell targets (Heidecke, Eckert, Schulze-Forster, & Maurer, 1997;.…”
Section: The Extracellular Role Of Protαmentioning
confidence: 52%
“…PTMS likely mediates immune function by blocking the effects of prothymosin alpha (50), and reduces the production of IL-2 and IL-2R (IL-2 receptor) required for proliferation of CD4+ T cells (51, 52). As a pro-inflammatory cytokine, IL-2 stimulates lymphocytes, monocytes, lymphokine-activated killer cells, and natural killer cells critical to immune function (53).…”
Section: 4 Discussionmentioning
confidence: 99%
“…The initial observations came from in vivo studies in animals, where proT was able to protect immunosuppressed mice against infections caused by Candida albicans and other opportunistic infections [30]. When added in lymphocyte cultures, proT enhanced antigen or mitogen-induced T cell proliferation, increased the production of interleukin (IL)-2 and the expression (both in number and in density) of its receptor on T cells [31,32] and upregulated major histocompatibility complex (MHC) class II antigen expression on human monocytes [33]. ProT was also shown to stimulate the cytotoxicity of natural killer (NK) cells [34] and the induction of lymphokine-activated killer (LAK) cells activity [35].…”
Section: The Dual-intracellular and Extracellular-role Of Protmentioning
confidence: 99%